Islands Apart: Explaining the Chinese Experience in the Philippines - Masucol, Ethan; Jap, Jangai; Liu, Amy H. (Frontiers in Political Science, 2022)
What explains the general absence of disdain against the Chinese Filipino community in the Philippines? One common answer focuses on the high rates of intermarriage—a legacy of Spanish colonialism. Yet, this explanation ignores how the Chinese were explicitly targeted—culturally during the American occupation and economically in the aftermath of independence. Moreover, it runs against theoretical expectations that when there are national security threats, there is a domestic backlash in the threatened state against the diaspora from the aggressor state. Simply put, we should observe rising discrimination against the Chinese-Filipinos given escalating maritime disputes between Manila and Beijing in the West Philippine Sea. Yet we do not. In this paper, we argue current patterns of minimal discrimination is the product of government–tempered nationalism. Despite the territorial conflicts, the Duterte administration has gone to great lengths to highlight the positive economic aspects between the two countries. To test this argument, we employ an original survey data, scrape speeches by government officials, and conduct interviews with local officials and business leaders.